Assessment of knowledge and attitude towards emergency contraception among postnatal mothers in Bruhat Bengaluru Mahanagara Palike referral hospital - Chethana, Ramegowda; Thejaswini, Puttaiah (International Journal Of Community Medicine And Public Health, 2018)
Background: Unintended pregnancy is an important public health issue in developing countries like India. Emergency contraception (EC) is one of the method for preventing such pregnancies. Awareness regarding EC is necessary for postnatal mothers since delay in contraceptive use during postpartum period until return of menstruation might subject them to risk of unintended pregnancy. Hence, the present study was undertaken. Methods: The study was conducted at Bruhat Bengaluru Mahanagara Palike (BBMP) referral hospital, Bengaluru from March 2016 to May 2016. A total of 100 postnatal mothers, were included in the study. A pre-tested semi-structured proforma was administered and information about socio-demographic profile, knowledge and attitude towards use of emergency contraception was obtained. Results: Among the study subjects, 28% were aware of emergency contraception, friends (57%) were the major source of information about EC. Overall knowledge regarding methods, time limit and dosage was low. There was a significant association between the educational level (p=0.01) and previous planned delivery (p<0.001) with awareness about EC. 51.4% had favourable attitude towards its use as an additional contraception whenever necessary. Conclusions: There is lack of knowledge and unfavourable attitude towards EC among post natal mothers.The factors such as education and previous planned deliveries had significant association with the awareness about EC. Hence health education regarding emergency contraception is necessary.